(untitled) - shreya singh, sujata josh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
distribution processes within an organization. However, the creation of business value through the adoption of information system strategies has been questionable and a major topic for research. The objective of this research paper is to critically analyse how Air Asia, a leading low fare airline, has been strategically implementing Information System (IS) to produce business values. The paper involves a qualitative analysis of secondary research data gathered from different sources and assessing it to meet the research objective. The analysis of the secondary research is based on four elements, Information System implementation methods, various information systems implemented at Air Asia, business values created through these systems, and creation of competitive advantage for the firm. This study will help managers gain insight as to how an efficient IS when strategically implemented can create competitive edge..